MODERN PEDAGOGICAL MECHANISMS FOR FORMING PRIMARY SCHOOL STUDENTS’ INDEPENDENT THINKING SKILLS IN THE EDUCATIONAL PROCESS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines modern pedagogical mechanisms for forming independent thinking skills among primary school students within the educational process. The study is grounded in the idea that independent thinking constitutes a core educational outcome in contemporary primary education, as it enables learners to analyze information, compare ideas, make reasoned judgments, solve practical and cognitive problems, and demonstrate initiative in learning situations. The paper explores the pedagogical value of learner-centered instruction, problem-based tasks, dialogic interaction, reflective activities, collaborative learning, formative assessment, and interdisciplinary integration as effective mechanisms for stimulating intellectual autonomy in young learners. Particular attention is given to the age-specific psychological and didactic features of primary school children, which require the use of flexible, development-oriented, and motivationally rich teaching strategies. The article argues that independent thinking does not emerge spontaneously, but is formed through purposefully organized educational conditions in which the teacher acts as a facilitator, guide, and creator of cognitively stimulating environments. The study also highlights the importance of encouraging questioning, hypothesis-building, interpretation, creative reasoning, and self-evaluation in classroom practice. As a result, the formation of independent thinking skills is presented not only as a methodological task, but also as a strategic priority for improving the quality of primary education. The findings may be used in teacher education, curriculum design, and the modernization of pedagogical practice in primary schooling.
Keywords: Independent thinking, primary education, pedagogical mechanisms, learner-centered instruction, cognitive activity, problem-based learning, reflective skills, critical reasoning, educational process, formative assessment